Pulse protein quality and derived bioactive peptides - Nosworthy, Matthew G.; Yu, Bianyun; Zaharia, L. Irina; Medina, Gerardo; Patterson, Nii (Frontiers in Plant Science, 2025)
There is a growing consumer interest in sources of dietary protein that are plant-based. Pulse crops, such as lentils, beans, chickpeas, and peas, are gaining popularity due to their environmental sustainability, nutrient density, and functional attributes. The protein content and quality of pulses vary across different pulse classes and processing methods. The biological properties of the protein and the physiologically active peptides make pulse crops attractive as potentially functional or health-promoting foods. This review highlights the nutritional quality of pulse proteins as determined by the Protein Efficiency Ratio and Protein Digestibility Corrected Amino Acid Score as well as bioactive properties of specific bioactive peptides related to amelioration of hypertension and diabetes. Additionally, the use of proteomics platforms, such as mass spectrometry, in combination with bioinformatics tools, enables the identification and characterization of bioactive peptides in pulse crops. These technologies facilitate the development of pulse-derived products with enhanced nutritional values. Overall, the high nutritional quality of pulse-based proteins supports the benefits of pulse inclusion in the diet, which can also exert beneficial bioactivities resulting in improving outcomes in non-communicable diseases.